2013
DOI: 10.1179/1607845412y.0000000054
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of discriminative indices for iron deficiency anemia and β thalassemia trait in a Brazilian population

Abstract: To discriminate iron deficiency anemia (IDA) from β thalassemia trait (βTT), several indices obtained from modern blood count analyzers have been reported. Discrimination power of seven indices to differentiate between IDA and βTT, such as Green and King Index (GKI), RDW Index (RDWI), Srivastava Index (SRI), Mentzer Index (MI), Shine and Lal Index (SLI), Ehsani Index (EI), and Sirdah Index (SI), were evaluated. These indices were applied on 47 patients with βTT and on 289 patients with IDA, as confirmed by gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The sensitivity and specificity of RDWI in the detection of βTT were found 80.7% and 84.7%, respectively and the sensitivity and specificity for the detection of IDA were 84.7% and 80.7%, respectively. These results are consistent with the findings of other relevant studies 19,20…”
Section: Discussionsupporting
confidence: 94%
“…The sensitivity and specificity of RDWI in the detection of βTT were found 80.7% and 84.7%, respectively and the sensitivity and specificity for the detection of IDA were 84.7% and 80.7%, respectively. These results are consistent with the findings of other relevant studies 19,20…”
Section: Discussionsupporting
confidence: 94%
“…Januária Fonseca Matos et al studied the most reliable indices were GKI and RDWI, while SLI presented the lowest accuracy. 10 Sehgal K et al found that the new index "Sehgal index" and MI <14 met the requirements of both high sensitivity and high specificity to predict BTT irrespective of iron levels in a large number of patients studied both retrospectively and prospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in this research, the mean MCV was 61.8 fL, RDW 16.8% and erythrocyte count 5.24 (in 10 6 /μL), so the mean value of the index was 198.1. The difference of this research was that compared to Matos 15 and Huang 5 the mean MCV was the smallest one, RDW was the greatest one and the erythrocyte count was the smallest one. In other words, if the MCV value as the numerator was small it will generate a small index value, but if the RDW as the numerator was large and erythrocyte count as the denominator was small it can generate a large index value.…”
Section: Resultsmentioning
confidence: 66%
“…The formula of RDW index showed MCVxRDW/erythrocyte count. β thalassemia trait in the research of Matos 15 , showed a mean MCV of 63.7 fl, RDW 15.8%, and erythrocyte count 5.47 (in 10 6 /μL), so the mean value of the index was 181.9. In the research conducted by Huang 5 the mean MCV was 62.4 fl, RDW 15.6% and erythrocyte count 6.14 (in 10 6 /μL), so the mean value of the index was 158.5.…”
Section: Resultsmentioning
confidence: 95%